Peripheral disease contributes significantly to the level of disease activity in axial spondyloarthritis - Janneke J de Winter; Jacqueline E Paramarta; Henriëtte M de Jong; Marleen G van de Sande; Dominique L Baeten (RMD Open)
Objective Spondyloarthritis (SpA) can encompass axial, peripheral and extra-articular disease manifestations. Patients are classified as axial or peripheral SpA depending on the presence or absence of current back pain, independently of the other disease manifestations. Therefore, we aimed to assess the percentage of patients with axial SpA with peripheral disease and how this peripheral disease contributes to the overall disease activity.Methods Prevalence and disease activity of peripheral disease manifestations were assessed in a real-life observational cohort of 314 patients with the clinical diagnosis of SpA and fulfilling the Assessment of SpondyloArthritis international Society (ASAS) criteria.Results Of the 314 patients fulfilling the ASAS criteria, 230 fulfilled the axial and 84 the peripheral SpA criteria. Of the 230 patients with axial SpA, 49% had purely axial disease without peripheral disease manifestations whereas 51% had combined axial (back pain) and peripheral (arthritis, enthesitis and/or dactylitis) disease. The latter group had the highest disease activity in comparison with pure axial SpA as well as with peripheral SpA.Conclusion Half of the patients classified as axial SpA according to the ASAS criteria also have peripheral disease manifestations such as arthritis, enthesitis and/or dactylitis. These peripheral disease manifestations contribute significantly to overall disease activity.